Meta Analisis: Pengaruh Model Keterpaduan Tipe Webbed Terhadap Pengetahuan dan Keterampilan IPA Peserta Didik - Risma, Mutia; Khair, Nyswatul; Nafsih, Nurul Zakiatin (Jurnal Penelitian Pembelajaran Fisika, 2020)
This study aims to analyze and compare the effect of the webbed model on science learning in terms of education levels, learning material / themes, learners' knowledge and skills. This study uses a meta-analysis method that examines 13 articles. Journal criteria used are national journals consisting of 11 articles and international journals consisting of 2 articles. Based on the results of the study, it can be understood that: 1) The integrated model of webbed type is more effectively applied at the junior high school level with an effect size value of 0.59 (medium category). 2) Webbed-type integration model is more effective to use on heat material / themes with an effect size value of 0.82 (high category). 3) Webbed type integration model is more effective to be used to improve students' science process skills with an effect size value of 0.58 (medium category).